The Main Factors Causing the Incidence of Diarrhea in Children: A Meta-Analysis - Eny Rohmawaty; R. Azizah (Poltekkes Kemenkes Palu, 2023)
Environmental factors that cause diarrhea are still under-researched, so researchers are interested analyze the risk factors for the availability of clean water, hand washing, mother's knowledge and the latrine conditions that affect the incidence of diarrhea in toddlers. The meta-analysis method was used in this study with the PICOS technique. Some of the data sources used are Google Scholar, Research Gate and Plos ONE by looking at keywords such as